Studi Pemberian Pupuk Majemuk Dan Campuran Tanah Gambut dengan Tanah Mineral Terhadap Pertumbuhan Anakan Durian (Durio Murr) - Yos Andy Tangkasiang (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
Study of Effect of compound fertilizer and mixture of peat soil with mineral soil on growth of Durian (Durio Murr) tillers. The aim is to determine the levels of compound fertilizer and the comparison of mineral soil mixtures that have the best influence on the growth of Durian tillers. Time used for three months. Complete Random Design with two factors. The first factor is compound fertilizer (P) composition of N, P and K content 16: 16: 16. The levels tested are four, namely 0 gram (p0), 1 gram (p1), 2 gram (p2) and 3 gram (p3) per poly bag. The second factor is the mixture of peat soil with mineral soil (T) with 4 comparisons: without mineral soil + 100% peat (t0), 5% mineral soil + 95% peat soil (t1), 10% mineral soil + 90% peat soil (t2 ), 15% mineral soil + 85% peat soil (t3). The results of the experiments that have been conducted can be concluded: The effect of interaction between mineral soil and compound fertilizer only occurs on increasing diameter and root wet weight. The parameters of leaf number, height increase, shoot wet weight and root dry weight, interactions were not significantly different. Interactively, the best effect is given by t2p1 = 23.33 mm on increasing diameter. The root wet weight is given by t2p1 = 7.5 grams. Independently mineral soil 5-10% of the polybag provides the best average value of growth against the test parameters. Compound fertilizer provides the best average value at the level of 1-2 grams of compound fertilizer / polybag.